The golden age of piracy the truth behind pirate myths - Little, Benerson 1959- (Skyhorse Publishing, 2016)
For thousands of years, pirates have terrorized the ocean voyager and the coastal inhabitant, plundered ship and shore, and wrought havoc on the lives and livelihoods of rich and poor alike. Around these desperate men has grown a body of myths and legends--fascinating tales that today strongly influence our notions of pirates and piracy. Most of these myths derive from the pirates of the "Golden Age," from roughly 1655 to 1725. This was the age of the Spanish Main, of Henry Morgan and Blackbeard, of Bartholomew Sharp and Bartholomew Roberts. The history of pirate myth is rich in action, at sea